PRODUCTION OF INDUSTRIALLY IMPORTANT ENZYMES BY THERMOBACILLI ISOLATED FROM HOT SPRINGS OF INDIA - DHYANI, ASHISH; GURURANI, RITU; SELIM, SAMY A.; ADHIKARI, PRIYANKA; SHARMA, AVINASH; PANDE, VEENA; PANDEY, ANITA (Research in Biotechnology, 2017)
Enzymes from thermophilic bacteria have received great attention for their potential applications in various industrial sectors. The present study deals with the production of five thermozymes (amylase, lipase, xylanase, protease and cellulase) from 10 thermophilic bacterial species, originally isolated from two hot springs namely Soldhar and Ringigad in Uttarakhand Himalaya, India. The bacterial isolate GBPI_25 produced maximum amylase (1217.86 U/ml) at 45 °C and 5 pH, GBPI 3 produced maximum lipase (22.59 U/ml) at 65 °C and 9 pH, GBPI_25 produced maximum xylanase (98.07 U/ml) at45 °C and 9 pH, GBPI_35 produced maximum protease (16.66 U/ml) at 55 °C and 9 pH, and GBPI 4 produced maximum cellulose (108.68 U/ml) at 45 °C and 5 pH. Crude enzyme preparations showed thermal and pH activities at broad temperature and pH range between 10-100 °C and 3-11 pH, respectively, with different temperature and pH optima. Amylase, xylanase and cellulase showed maximum activity at 50 °C while lipase and protease showed higher activity at 40 and 60 °C, respectively. Enzyme activity at wide temperature range-cellulase and protease from 10-100 °C, amylase and xylanasefrom10-90 °C, and lipase activity from 10-80 °C were the remarkable records from this study. Similarly, pH range for amylase and lipase activity was recorded from 4-11, for xylanase from 3-9, and for protease and cellulase from 3-10. All the thermozymes showed maximum stability at 40 °C and pH 5 except cellulase that showed higher stability at40 °C and neutral pH.